Complement activation during cardiopulmonary bypass and association with clinical outcomes. Issue 1 (13th January 2022) - Kefalogianni, Rengina; Kamani, Farah; Gaspar, Mihaela; Aw, TC; Donovan, Jackie; Laffan, Mike; Pickering, Matthew C.; Arachchillage, Deepa J.
Abstract: In this prospective, single‐centre observational study of 30 patients undergoing cardiopulmonary bypass (CPB), the effect of unfractionated heparin (UFH), CPB surgery and protamine sulphate on complement and on post‐operative blood loss were assessed. Although C3 and C4 levels decreased significantly immediately following the administration of UFH, C3a, C5a, Bb fragment and SC5b‐9 remained unchanged. During CPB, C3 and C4 continued to fall whilst both alternative and classical pathways activation markers, Bb, C3a, C5a and SC5b‐9 increased significantly. Protamine sulphate had no effect on classical pathway components or activation markers but decreased alternative pathway activation marker Bb. Over the 12–24 h post‐surgery, both classical and alternative pathway activation markers returned to baseline, whilst C3 and C4 levels increased significantly but not to baseline values. Total drain volume 24 h after the surgery showed a moderate inverse correlation with post‐protamine C3 ( r  = −0.46, p  = 0.01) and C4 ( r  = −0.57, p  = 0.0009) levels, whilst a moderate positive correlation was observed with post‐protamine C3a ( r  = 0.46, p  = 0.009), C5a ( r  = 0.37, p  = 0.04) and SC5b‐9 ( r  = 0.56, p  = 0.001) levels but not with Bb fragment ( r  = 0.25, p  = 0.17). Thus, inhibition of complement activation may be a therapeutic intervention to reduce post‐operative blood in patients undergoing CPB.